Adipokinetic Hormone Receptor Mediates Trehalose Homeostasis to Promote Vitellogenin Uptake by Oocytes in Nilaparvata lugens - Lu, Kai; Wang, Ying; Chen, Xia; Zhang, Xinyu; Li, Wenru; Cheng, Yibei; Li, Yue; Zhou, Jinming; You, Keke; Song, Yuanyuan; Zhou, Qiang; Zeng, Rensen (Frontiers in Physiology, 2019)
Adipokinetic hormones (AKHs) are well known to mobilize lipids and carbohydrates for energy-consuming activities in insects. These neuropeptides exert their functions by interacting with AKH receptors (AKHRs) located on the plasma membrane of fat body cells, which regulates energy mobilization by stimulating lipolysis of triacylgylcerols (TAG) to diacylglycerols (DAG) and conversion of glycogen into trehalose. Here, we investigated the roles of AKH/AKHR signaling system in trehalose metabolism and vitellogenesis during female reproduction in the brown planthopper, Nilaparvata lugens. Knockdown of AKHR expression by RNA interference (RNAi) resulted in a decrease of the circulating trehalose in hemolymph and significantly increased levels of two trehalases in fat bodies, indicating that the modulation of hemolymph trehalose levels by AKHR may be mediated by regulating trehalose degradation. In addition, adult females that had been injected with double-stranded RNA (dsRNA) for AKHR exhibited delayed oocyte maturation, prolonged pre-oviposition period, as well as decline in egg number and reduction in fecundity. Considering that these phenotypes resulting from AKHR silencing are similar to those of vitellogenin receptor (VgR) RNAi, we further analyzed a possible connection between AKHR and vitellogenesis. Knockdown of AKHR showed no effects on the Vg synthesis in fat bodies, whereas it significantly reduced the levels of VgR in ovaries. With RNAi-females, we observed an increase of Vg accumulation in hemolymph and a decrease of Vg deposition in ovaries. Moreover, the decrease in VgR expression and Vg incorporation by developing oocytes could be partially rescued by injection of trehalose into AKHR RNAi females. The present study has implicated trehalose in the AKH/AKHR signaling-mediated control of reproduction and provided new insight into mechanisms of AKH/AKHR regulation of trehalose metabolism in insect vitellogenesis, oocyte maturation and fecundity.